Successful emergency department interventions that reduce time to antibiotics in febrile pediatric cancer patients. Issue 1 (7th March 2017) - Spencer, Sandra; Nypaver, MIchele; Hebert, Katherine; Benner, Christopher; Stanley, Rachel; Cohen, Daniel; Rogers, Alexander; Goldstick, Jason; Mahajan, Prashant
Abstract : Children with cancer and fever are at high risk for sepsis related death. Rapid antibiotic delivery (< 60 minutes) has been shown to reduce mortality. We compared patient outcomes and describe interventions from three separate quality improvement (QI) projects conducted in three United States (US) tertiary care pediatric emergency departments (EDs) with the shared aim to reduce time to antibiotic (TTA) to < 60 minutes in febrile pediatric oncology patients (Temperature > 38.0 C). A secondary objective was to identify interventions amenable to translation to other centers. We conducted a post project analysis of prospectively collected observational data from children < 18 years visiting these EDs during independently conducted QI projects. Comparisons were made pre to post intervention periods within each institution. All interventions were derived independently using QI methods by each institution. Successful as well as unsuccessful interventions were described and common interventions adopted by all sites identified. A total of 1032 ED patient visits were identified from the three projects. Improvement in median TTA delivery (min) pre to post intervention(s) was 118.5–57.0 at site 1, 163.0–97.5 at site 2, and 188.0–111.5 at site 3 (p<.001 all sites). The eight common interventions were 1) Triage application of topical anesthetic 2) Rapid room placement & triage 3) Resuscitation room placement of ill appearing children 4) Close proximity to central line equipment 5) Antibiotic administration before laboratory analyses 6) Consensus clinical practice guideline establishment 7) Family pre-ED education for fever and 8) Staff project updates. This core set of eight low cost, high yield QI interventions were developed independently by the three ED's which led to substantial reduction in time to antibiotic delivery in children with cancer presenting with fever. These interventions may inform future QI initiatives in other settings caring for febrile pediatric oncology patients.